2009
DOI: 10.2320/matertrans.mra2008407
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Optical Characteristics of BaTiO<SUB>3</SUB>:Yb<SUP>3+</SUP> Powders

Abstract: Yb3þ doped Barium Titanate powders were prepared by the sol-gel method in order to study their structural and luminescent properties. These powders have potential to be used to prepare films for luminescent screens. The synthesized powders were obtained at 2, 4 and 8% mol Yb 3þ doped BaTiO 3 . In order to determine organic compound decomposition, weight loss, and establish the crystallization process, we performed TGA and DTA analyses. The powders were also thermally treated at temperatures ranging from 700 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Intermediate lanthanide ions, such as Dy 3+ , Ho 3+ and Er 3+ exhibit an amphoteric site-occupation preference for both the A and B sites 29,47,48 whereas the smallest rare earth ions, such as Yb 3+ and Lu 3+ occupy preferentially the B sites 49,50 in the Ln-doped BaTiO 3 nanocubes series, the lanthanoid contraction will lead to sizes of these ions comparable to that of Ti 4+ enabling substitutions could occur at both A- and B-sites. 51–53 A detailed study of the substitutional mechanism in Ln-doped BaTiO 3 nanocrystals, as well as the analysis of the emission spectra are currently underway and will be presented in a forthcoming paper.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Intermediate lanthanide ions, such as Dy 3+ , Ho 3+ and Er 3+ exhibit an amphoteric site-occupation preference for both the A and B sites 29,47,48 whereas the smallest rare earth ions, such as Yb 3+ and Lu 3+ occupy preferentially the B sites 49,50 in the Ln-doped BaTiO 3 nanocubes series, the lanthanoid contraction will lead to sizes of these ions comparable to that of Ti 4+ enabling substitutions could occur at both A- and B-sites. 51–53 A detailed study of the substitutional mechanism in Ln-doped BaTiO 3 nanocrystals, as well as the analysis of the emission spectra are currently underway and will be presented in a forthcoming paper.…”
Section: Resultsmentioning
confidence: 99%
“…doped BaTiO 3 nanocubes series, the lanthanoid contraction will lead to sizes of these ions comparable to that of Ti 4+ enabling substitutions could occur at both A-and B-sites. [51][52][53] A detailed study of the substitutional mechanism in Lndoped BaTiO 3 nanocrystals, as well as the analysis of the emission spectra are currently underway and will be presented in a forthcoming paper. Various reports published in the literature have suggested that the doping of dielectric perovskites with lanthanoid ions leads to a drastic enhancement of their dielectric properties.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation